EFEKTIVITAS PROGRAM BERAS SEJAHTERA DALAM MENINGKATKAN TARAF HIDUP MASYARAKAT DI KECAMATAN JAILOLO KABUPATEN HALMAHERA BARAT - BOBANE, KERIN VIDIYANTI; LENGKONG, FLORENCE DAICY; LONDA, VERY (Sam Ratulangi University, 2018)
Prosperous rice is a food subsidy in the form of rice intended for low-income households as an effort from thegovernment to increase food security and provide social protection to targeted households. The success of theProsperous Rice Program is measured by the level of achievement of the 6T indicator, namely: on target. Exactamount, right price, timely, proper quality, and proper administration. This program aims to reduce the burdenof Household Goal expenditure (RTS) through the fulfillment of some basic food needs in the form of rice andprevent the decline in energy and protein consumption. The purpose of this study is to determine the extent ofeffectiveness of Rice Prosperous Program in improving Pre-Prosperous People's Welfare in District JailoloWest Halmahera District. Data Collection Techniques in this study are through: Observation ie directobservation to the location of research, conduct Interview and Documentation.The results showed that the prosperous rice program in Kecamatan Jailolo has not been effective because thereare still some inappropriate things such as the data of the recipient of the program has not been updated, thegovernment does not involve the community so that the community does not know clearly the price and theactual amount of rice. Likewise, there are additional budgets that are imposed on the community by reason oftransportation money for rice transport vehicles and supervision from sub-district governments that are stilllacking in the level of coordination between the government and the community.Keywords : Effectiveness, Improving, Living Level